FMEA Method as a Quality Solution of Welding Machine SMAW Type 400 SX: Metode FMEA Sebagai Solusi Kualitas Hasil Pengelasan Mesin SMAW Type 400 SX - Roberth M. Ratlalan (Jurnal Sains dan Teknik Terapan, 2023)
Maintenance is a series of activities to maintain facilities and equipment so that they are always ready to use to carry out production effectively and efficiently according to a predetermined schedule and based on standards (functional and quality). FMEA (Failure Mode Effect Analysis) is a method of evaluating the possibility of a failure of a system, design, process or service to make steps to deal with it. SMAW welding where heat from welding is generated by an electric arc between a flux-shielded supplied electrode and the workpiece. The results of calculations using the FMEA table to determine the critical components of the SMAW Type 400 SX Welding machine obtained 1 critical component, then calculating the impact score (Severity), possibility (Occuration), Detection. Then, Intermediate Decision Tree (IDT) and Logic Tree Analysis (LTA) analyzes were carried out. In the final stage, a Standard Operating Procedure (SOP) was determined to determine the maintenance of the SMAW Type 400 SX Welding machine.